Analytical procedures for the determination of estrogen compounds in a surface water reservoir in Southeast Brazil - Cais, Thayná Aparecida; Procópio, Alley Michael da Silva; Kondo, Márcia Matiko; Silva, Flávio Soares; de Andrade, Sandro José (Eclética Química, 2021)
In this study, an analytical methodology was validated to determine and quantify four estrogen hormones using high-performance liquid chromatography (HPLC) with detections by diode array detector (DAD) and by fluorescence detector (FLD). For validation of the method, the following parameters were evaluated: linearity, selectivity, precision, accuracy, limit of detection (LOD), limit of quantification (LOQ) and robustness. Environmental samples were preconcentrated using solid phase extractions and for that, an experimental design was planned to determine the best recovery conditions by varying cartridge types, flow of eluent, pH of the samples, and eluting solvent. Five surface water sampling campaigns were carried out in five different sites of Furnas Reservoir over the months of December 2015 and May 2016. Sample point 1 was located near the sewage treatment plant of the city of Alfenas - MG, while sample point 5 was the most distant from this location. All estrogens, except for E1, were found in all water samples of at least one of the sampling sites. The concentrations of E3, E2 and EE2 ranged from 11-366, 63-422 and 75-9998 ng L-1, respectively. These results are consistent with several studies published in the scientific literature.